2014
DOI: 10.1002/jqs.2741
|View full text |Cite
|
Sign up to set email alerts
|

Individual glass shard trace element analyses confirm that all known Toba tephra reported from India is from the c. 75‐ka Youngest Toba eruption

Abstract: Uncertainty over the identity and age of Toba tephras across peninsular India persists, with radiometric age dates contradicting earlier compositional data, which have been used to identify this important stratigraphic marker as the Youngest Toba Tuff (YTT). To address this issue, new single glass shard analyses have been performed for samples from Morgaon and Bori (north‐western India), which have recently been dated at c. 800 ka. These, and indeed all Toba tephra samples thus far analysed from India, show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…Geochemical analyses of India tephra deposits have confirmed the presence of YTT in the Jurreru, Son, Purna, Mahanadi, Kukdi, Vansadhara, Barakar and Narmada Valleys (Acharyya and Basu, 1993;Shane et al, 1995;Westgate et al, 1998;Petraglia et al, 2007Petraglia et al, , 2012Pearce et al, 2014). Ash deposits identified in a number of other valleys are assumed to also comprise YTT horizons, such as in the Indravati, Brahmani, and Nagavali valleys (Acharyya and Basu, 1993), although some investigators consider that ash in some sites in India correlate with the 0.84 Ma Older Toba Tuff (OTT) (Westaway et al, 2011).…”
Section: Introductionmentioning
confidence: 81%
“…Geochemical analyses of India tephra deposits have confirmed the presence of YTT in the Jurreru, Son, Purna, Mahanadi, Kukdi, Vansadhara, Barakar and Narmada Valleys (Acharyya and Basu, 1993;Shane et al, 1995;Westgate et al, 1998;Petraglia et al, 2007Petraglia et al, , 2012Pearce et al, 2014). Ash deposits identified in a number of other valleys are assumed to also comprise YTT horizons, such as in the Indravati, Brahmani, and Nagavali valleys (Acharyya and Basu, 1993), although some investigators consider that ash in some sites in India correlate with the 0.84 Ma Older Toba Tuff (OTT) (Westaway et al, 2011).…”
Section: Introductionmentioning
confidence: 81%
“…When Ba and Sr concentrations are plotted against many other incompatible elements (e.g. Rb, Cs, Nb, Ta, Zr, Hf, U, Th, REE), MTT and YTT consist of several glass shard populations (Westgate et al , ; Pearce et al , ; Westgate and Pearce, ). These are distinct within individual eruptions, but show some overlap between eruptions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Assigning distal Toba tephra to a particular eruption using glass shard major element compositional data has proved difficult because OTT, MTT and YTT have almost identical compositions (Westgate et al , ; Smith et al , ; Gatti et al , ). Nonetheless, some have suggested that major element discrimination is possible; for example, by using FeO (Westaway et al , ), but this has subsequently been discounted (Gatti et al , ; Pearce et al , ; Westgate and Pearce, ). Biotite major element composition provides a means to distinguish these eruptions (Smith et al , ), and biotite is often found in distal deposits, where small flakes travel easily within the eruption cloud.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations